ADAPTIVE OPERATION AND MAINTENANCE STRATEGIES FOR ENHANCING THE PERFORMANCE OF ROOFTOP PV SYSTEMS IN HARSH DESERT CLIMATES: A CASE STUDY OF SAUDI ARABIA - Muhammad Ibrahim; Abdullah; Saad Ud Din; Qaiser Iqbal; Attaullah Shah (Spectrum of Engineering Sciences, 2025)
This paper discusses adaptive operation and maintenance (O&M) techniques to enhance the performance of rooftop photovoltaic (PV) systems under extremely hot climatic conditions in Saudi Arabia. Although solar irradiance is high, several environmental factors, including dust, intense heat, and high humidity found in this region, significantly impact the performance and lifetime of the system. The study assesses the performance of smart technologies, such as the use of AI in predictive maintenance, robotic cleaning technology, and Internet of Things-facilitated monitoring systems. Performance ratio (PR), the utilization factor, and Levelized Cost of Electricity (LCOE), among the key performance indicators, are subdivided into two parts, starting with the case studies of Riyadh and Dhahran cities. The results suggest that adaptive O&M strategies could enable energy production, resulting in at least a 12 percent increase, sustain PRs above 90 percent, and reduce LCOE to a low of 0.014/kWh. The adaptive approaches are cheaper and more effective as compared to reactive concepts. The paper ends with suggestions on how to incorporate the intelligent O&M practice into real life and the gaps in future research on the matter of desert PV implementation across the MENA region.